THE EFFECTS OF INTEREST RATE AND MONEY SUPPLY ON SYSTEMATIC RISK ASSOCIATED WITH RETURN IN NIGERIAN EXCHANGE - Rofiat Adedokun; Prof. Sani Abdullahi; Dr. Ibrahim Mohammed; Prof. Ahmad Dogarawa (Gusau Journal of Accounting and Finance)
Stock market investors are largely compensated for taking systematic risks as idiosyncratic are controlled through effective portfolio construction but systematic risk cannot be diversified. As such, there is increasing concern among academics to understand systematic risks and its determinants in emerging markets. Hence, the need to investigate the effect of interest rate and money supply as determinants of systematic risk associated with return in the Nigerian Exchange. The study was correlational in nature, and data for the study was collected from the CBN statistical bulletin and the Nigerian Exchange. Monthly data from April, 2012 to December, 2022 were used for the analysis. The study conducted data analysis using autoregressive distributive lag model and other preliminary analysis. Result from the study revealed that money supply has positive significant effect on systematic risk. On the other hand, interest rate exhibited negative and statistically insignificant effect on systematic risk. The study came to the conclusion that money supply is a determinant of systematic risk as it can influence its behaviour significantly while interest rate can affect systematic risk but the magnitude is statistically insignificant. Therefore, the study recommended that investors should continuously study the changes in the behaviour of the determinants in order to make sound investment decision and maximize their return from the market. The government through the CBN should also ensure that they consistently improve their policies on interest rate and money supply. This will help the market to operate efficiently.